Inhibitory Effects of Twenty-Nine Compounds From Potentilla longifolia on Lipid Accumulation and Their Mechanisms in 3T3-L1 Cells - Ma, Qianqian; Ye, Li; Li, Wei; Lin, Shengxi; Zhao, Xiaoyan; Jin, Chenghua; Liu, Guancheng; Liu, Huan; Sun, Yunpeng; Yuan, Haidan; Piao, Guangchun (Frontiers in Pharmacology, 2020)
ABSTRACT: Potentilla longifolia Willd. ex D.F.K.Schltdl., which is a kind of traditional Chinese herb, is often referred to as “Ganyancao” in China, which means “the herb is effective in the treatment of liver inflammation”. Three new (ganyearmcaoosides A and B and ganyearmcaoic acid A; 1–3) and 26 known compounds (4–29) were isolated from the 95% ethanol extract of the dried aerial parts of this plant, of which 23 were isolated for the first time from this plant. The chemical structures of these compounds were elucidated using NMR and HR-ESI-MS analysis. The inhibitory effects of the 29 compounds with safe concentrations on the lipid accumulation in 3T3-L1 cells were evaluated using photographic and quantitative assessments of lipid contents by Oil Red O staining, and measurement of the triglyceride levels. Comprehensive analysis showed that compound 12 (3,8-dimethoxy-5,7,4'- trihydroxyflavone) showed the best inhibitory effect on lipid accumulation such as reducing the accumulation of oil droplets and triglyceride level, and was superior to the reference in positive control. Western blot analysis and RT-PCR results showed that compound 12 enhanced the phosphorylations of AMPK and ACC, and inhibited the expressions of adipogenesis-related proteins or genes including SREBP1c, FAS, SCD1, GPAT, PPARγ and C/EBPα, and thereby significantly inhibited lipid accumulation in a concentration-dependent manner. P. longifolia and its bioactive compounds could be promising as potential therapeutic agents for diseases related to lipid accumulation in the future.